Cultural Objects Name Authority® Online - Getty Research Institute (2012)
[Dt.:] Der Thesaurus des Getty Research Institutes zu kulturellen Objekten und Kunstwerken. - [Engl.:] CONA, a new vocabulary now accepting contributions, includes titles, attributions, and other information for art and architecture